Sources of Ethnic Inequality in Vietnam - van de Walle, Dominique; Gunewardena, Dileni (World Bank, Washington, DC, 2015)
Vietnam's ethnic minorities, who tend to live mostly in remote rural areas, typically have lower living standards than the ethnic majority. How much is this because of differences in economic characteristics (such as education levels and land) rather than low returns to characteristics? Is there a self-reinforcing culture of poverty in the minority groups, reflecting patterns of past discrimination? The authors find that differences in levels of living are due in part to the fact that the minorities live in less productive areas characterized by difficult terrain, poor infrastructure, less access to off-farm work and the market economy, and inferior access to education. Geographic disparities tend to persist because of immobility and regional differences in living standards. But the authors also find large differences within geographical areas even after controlling for household characteristics. They find differences in returns to productive characteristics to be the most important explanation for ethnic inequality. But the minorities do not obtain lower returns to all characteristics. There is evidence of compensating behavior. For example, pure returns to location--even in remote, inhospitable areas--tend to be higher for minorities, though not high enough to overcome the large consumption difference with the majority. The majority ethnic groups' model of income generation is a poor guide on how to fight poverty among ethnic minority groups. Nor is it enough to target poor areas to redress ethnic inequality. Policies must be designed to reach minority households in poor areas and to explicitly recognize behavior patterns (including compensating behavior) that have served the minorities well in the short term but intensify ethnic inequalities in the longer term. It will be important to open up options for minority groups both by ensuring that they are not disadvantaged (in labor markets, for example), and by changing the conditions that have caused their isolation and social exclusion.